Counseling on the Use of Environmental Information for Malaria Case Prevention in the Resettlement Area of Osi Island, West Seram Regency - Manusiwa, Aprilia E; Leuwol, Ferdinand Salomo; Salakory, Melianus (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
On April 6, 2022, the number of new Covid-19 cases reached 2,400 within a span of 7 days. It's anticipated that this figure will decrease as human immunity strengthens. Comorbidities in infected individuals might contribute to a decline in the immune system. In the Covid-19 pandemic era, it's crucial to implement education focusing on healthy behavior changes, utilizing a risk communication approach in prevention, treatment, and recovery stages in environments susceptible to malaria within the village community of Pulau Osi. The education program aims to enhance public understanding of the health risks and threats, empowering them to take appropriate actions to shield themselves from potential health issues. Employing Project-Based Learning as the approach for pest control education, trained JUMANTIK agents possess the necessary knowledge and skills to prevent malaria.